Strategi Pembelajaran Mendalam PAI Dalam Mengembangkan Kemampuan Berpikir Kritis Siswa SMA Terhadap Informasi Keagaamaan - Imam Qosthalani; Muhammad Irfan; Sabillah Aiska; Syifa Karimah putri; Abdul Fadhil (Advances In Education Journal, 2025)
This research discusses deep learning strategies in Islamic Religious Education (PAI) to develop high school students critical thinking skills regarding religious information. The main issues addressed include challenges in PAI teaching that focus excessively on memorization and insufficient stimulation of critical thinking, as well as the need for methods that support deep understanding. This study aims to analyze effective deep learning strategies to enhance students critical thinking skills within the PAI context. The research employs a library research method with a descriptive-analytical approach by examining academic literature and previous studies related to deep learning strategies and critical thinking in PAI. Results indicate that inquiry-based learning, collaborative discussion, reflective learning, and project-based learning improve students abilities to analyze, evaluate, and synthesize religious information while fostering balanced attitudes toward religious perspectives. The findings recommend integrating deep learning approaches into the PAI curriculum to promote more meaningful, reflective, and context-based learning.